Synthesis, photophysical properties and two-photon absorption study of tetraazachrysene-based N-heteroacenes - Li, Gang (2021)
Three novel N-heteroacene molecules (SDNU-1, SDNU-2 and SDNU-3) based on tetraazachrysene units as cores have been designed, synthesized and fully characterized. Their photophysical, electrochemical and fluorescence properties were investigated, and they exhibited blue to green emission in the solid state. Interestingly, SDNU-2 exhibited high solid photoluminescence quantum efficiencies (75.3 %), which is the highest value of N-heteroacenes derivatives to date. Two-photon absorption studies have been conducted by using the open and close aperture Z-san technique. SDNU-3 showed a significant enhancement in the two-photon absorption cross-section with magnitudes as high as about 700 GM (1 GM = 1×10⁻⁵⁰ cm⁴s/photon) when excited with 800 nm light, which is the largest value based on a heteroacene system measured by using a Z-scan experiment so far. We attribute the outcome to sufficient electronic coupling between the strong charge transfer of quadrupolar substituents and the tetraazachrysene core. Our result would provide a new guideline to design novel efficient two-photon materials based on N-heteroacene cores.